James Lind Alliance research priorities: what role do carbohydrates, fats and proteins have in the management of Type 2 diabetes, and are there risks and benefits associated with particular approaches?. Issue 3 (15th October 2018) - Dyson, P.; McArdle, P.; Mellor, D.; Guess, N.
Abstract: Aims: To assess the role played by carbohydrates, fat and proteins in the management of Type 2 diabetes. Background: Diabetes research tends to reflect the interests of academics or the pharmaceutical industry, rather than those of people living with Type 2 diabetes. The James Lind Alliance and Diabetes UK addressed this issue by defining the research priorities of people living with Type 2 diabetes. Three of the top 10 research priority questions focused on lifestyle. Methods: A narrative review was undertaken with a structured search strategy using three databases. Search terms included the three macronutrients and Type 2 diabetes. No restrictions were placed on macronutrient quantity or length of study follow‐up. Outcomes included changes in HbA1c, body weight, insulin sensitivity and cardiovascular risk. Results: There is no strong evidence that there is an optimal ratio of macronutrients for improving glycaemic control or reducing cardiovascular risk. Challenges included defining the independent effect of macronutrient manipulation and identifying the effects of macronutrients, independent of foods and dietary patterns. Extreme intakes of macronutrients may be associated with health risks. Conclusions: It is challenging to formulate food‐based guidelines from studies based on macronutrient manipulation. Structured education should be offered to support individuals in discovering their optimal, individual dietary approach. Recommendations for dietary guidelines should be expressed in terms of foods and not macronutrients.